Evolution of Hot Corrosion Behavior of YSZ‐Ta2O5 Composites with Different YSZ/Ta2O5 Ratios. (21st January 2014) - Habibi, Hamed; Guo, Shengmin
Abstract : This study compares the hot corrosion performance of yttria‐stabilized zirconia (YSZ)‐Ta2 O5 composite mixtures (TaYSZ) in the presence of molten mixture of Na2 SO4 + V2 O5 at 1100°C. The tested compositions vary from pure YSZ (0TaYSZ) to a Ta2 O5 ‐dominating (70 wt% Ta2 O5 + balance YSZ, 70TaYSZ) composite mixture with a gradual increase of Ta2 O5 . 50TaYSZ (50 wt% Ta2 O5 + balance YSZ) sample forms a highly stable zirconium tantalum oxide. 50TaYSZ is more stable, both thermally and chemically in Na2 SO4 +V2 O5 media at 1100°C, than other tested YSZ‐Ta2 O5 (TaYSZ) composites, and shows a good hot corrosion resistance.